228k views
3 votes
Expand and simplify.
3x(x-2)-2x(3x - 5)​

2 Answers

1 vote

Answer: -3
x^(2)+4x

Explanation:

=3
x^(2)-6x-6
x^(2)-10x

=-3
x^(2)+4x

User Footniko
by
5.2k points
3 votes

Answer:

To simplify, we can use the FOIL method. That stands for first, outer, inner, last. What we do is take two factors at a time and multiply the first terms by each other, the outer terms together, etc.

Let's start with (2x-1) and (x+5)

First: 2x * x = 2x^2

Outer: 2x * 5 = 10x

Inner: -1 * x = -x

Last: -1 * 5 = -5

2x^2 + 9x - 5

Now FOIL this result with (3x - 2)

6x^3 - 4x^2 + 27x^2 - 18x - 15x + 10

Simplify:

6x^3 - 23x^2 - 33x + 10

Explanation:

User Tommaso Capelli
by
5.3k points